The Jewish Study Bible - Aubrey L. Glazer (International Institute of Islamic Thought, 2005)
Jabès’ aphorism captures the challenge to readers of scripture: how to preserve the immaculate experience of the ineffable through a finite language of maculate perception. The Jewish Study Bible [JSB] is a testament to the human struggle with the divine as read through diverse interpretive lenses throughout the ages. Editors Berlin and Brettler, along with Fishbane, have compiled a first-rate Hebrew Bible that fuses the technically adept JPS English translation along with introductions, annotations, and essays by many of today’s established and burgeoning scholars. This model is based upon The New Oxford Annotated Bible (p. xi), which abridges in-depth essays by contemporary scholars into accessible versions for general readers and undergraduate students. The balance between North American and ...